Modulatory activity of the Copper chelate, Copper N-(2-Hydroxy acetophenone) glycinate, in ABC-transporter-expressing cell lines - Hartinger, Eva-Maria; Mahringer, Anne; Choudhuri, Soumitra Kumar; Fricker, Gert; Efferth, Thomas (Anticancer research, 2023)
Metal-containing compounds (e.g., platinum complexes) belong to the standard armamentarium of cancer chemotherapy. Copper N-(2-hydroxy acetophenone) glycinate (CuNG) exerts anticancer activity in vitro and in vivo and modulates drug resistance related to glutathione or P-glycoprotein. The potential of CuNG to interact with ATP-binding cassette (ABC) transporters has not been fully explored yet. This study focused on the modulatory effects of CuNG on four ABC transporters (MRP1, MRP1, BCRP, and P-glycoprotein).